OPTIMALISASI MANAJEMEN SISWA DALAM MENINGKATKAN PRESTASI NON AKADEMIK MADRASAH ALIYAH NEGERI 1 LAMPUNG TIMUR - Sri Ekowati (Hijri, 2025)
Student achievement is of great concern to society. Schools that are able to create student achievement are seen as positive schools, while schools that minimize student achievement are seen as negative schools. This research was designed using qualitative methods. The problem is discussed through field research at MAN 1 Lampung Timur to get thoughts related to optimizing student management in improving non-academic achievement. Research data were obtained by means of interviews, observations, and documentation studies. All data were analyzed, with interactive analysis through 3 activities, namely data reduction, data presentation, and conclusion drawing. The results showed that planning to improve non-academic achievement includes: (a) Identification of non-academic activities that are in accordance with the talents, interests and potential of students. (b) Socialization of non-academic activities. (c) Identification of supporting infrastructure for non-academic activities. Optimizing student management in improving non-academic achievement includes: (a) organizing non-academic activities that are in accordance with the talents, interests and potential of students. (b) encouraging student participation in organized non-academic activities. (c) grouping students in selected non-academic activities. (d) appointing non-academic activity coaches according to their competence. Evaluation of improving non-academics includes: (a) Written test. (b) Comparing the achievement of results.